Manajemen Strategi Dinas Pendidikan, Pemuda dan Olahraga dalam Penanggulangan Anak Putus Sekolah di Kabupaten Karawang - Regita Febriyanti (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study discusses the strategic management of the Department of Education, Youth and Sports (Disdikpora) in tackling dropouts in Karawang district. This study used descriptive qualitative method. Data collection techniques were carried out by triangulation which included interviews, documentation and observation, then analyzed through three stages, namely reduction, presentation and drawing conclusions. The theory used is Fred R. David's Strategic Management (2011). The results of this study are that the dropout rate in Karawang is mostly in coastal areas and the average level of students in Karawang only touches the 8th grade of junior high school. Various kinds of policies were made by the Disdikpora for the realization of basic compulsory education, such as the allocation of greater scholarships and improving the quality of education, but this has not been running optimally because negative indications are still being found from the implementation of overcoming the dropout rate in Karawang, corrective steps are taken by Disdikpora by empowering various parties to assist in the supervision and implementation of overcoming school dropouts in Karawang.